(untitled) (World Bulletin of Social Sciences, 2026)
In this research paper, the transformation of Japanese language education in Uzbekistan is examined within the broader framework of evolving Uzbek– Japanese relations. Since 2019, relations between Uzbekistan and Japan have entered a new strategic phase marked by intensified political dialogue, expanded economic cooperation, and strengthened institutional collaboration. Although significant attention has been directed toward labor mobility mechanisms, a deeper and more sustainable transformation is unfolding within the higher education sector. Japanese language education in Uzbekistan has progressed from a narrowly defined philological specialization into a strategically important academic field closely linked to international cooperation, research advancement, and university modernization. This study analyzes the development of Japanese language education between 2019 and 2025, taking into account recent bilateral agreements, high-level political initiatives, and academic partnerships. Particular emphasis is placed on the institutional role of universities and the leadership of the Uzbekistan State World Languages University in establishing and maintaining national standards in Japanese studies.